The use of effective microorganisms (EM) for pretreatment of wet market wastewater - Shahbuddin, Munira; Raus, Raha Bt. Ahmad; Ramli, Nur Amalina; Adel, Nahla; Jami, Mohammed Saedi; Zainuddin, Zaki (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Nature based solutions have received considerable attention for water and land quality restoration and potential for sustainability management. The use of naturally occurring permaculture of non-pathogenic microorganisms known as Effective Microorganisms (EM) have gain reputation in the past few years in the South East Asia due to its environmental friendly nature. The technology is not new and has been used in agriculture, restoration and rehabilitation of water resources, and animal housekeeping and husbandry for years in countries like Japan and Thailand. The use of chemicals for water treatment has been costly and detrimental to the environment. In this report, we present the results from the use of EM which we developed in our laboratory for the pretreatment of wastewater from Selayang wetmarket in Selangor. We examined the effects of EM use on the water quality based on the parameters of pH, DO, BOD5, COD, TSS and NH3-N. Improvements of the water quality before and after treatment were observed and quantified. It was proven that application of EM, the wastewater quality were reduced to its acceptable standards. Pretreatment with EM reduces expenditure and operational stress of the treatment plant. We also proposed a new design of EM treatment plant with detail specifications for the treatment to optimize the efficiency of EM in treating the wastewater from a wet market.